2010
DOI: 10.3109/10428190903552112
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressants maprotiline and fluoxetine have potent selective antiproliferative effects against Burkitt lymphoma independently of the norepinephrine and serotonin transporters

Abstract: The discovery that some selective serotonin transporter- (SSRI) and norepinephrine transporter- (NSRI) targeting antidepressants have the potential to act as anticancer agents adds greatly to their diverse pharmacological application. We report that the SSRI fluoxetine and the NSRI maprotiline are potent antiproliferative agents against human Burkitt lymphoma (BL), having little effect on normal blood cells. The results of this study show that although there is low-level expression of the norepinephrine transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 55 publications
1
52
0
Order By: Relevance
“…A number of novel pyridines, dihydropyridone and N,N-di(1-aryl-2-propyl) amines described as route-specific byproducts associated with clandestine synthesis of 4-MTA and related amphetamines 12 were previously evaluated for SERT-selective cytotoxicity using human embryonic kidney cells overexpressing SERT, and two malignant cell lines; the DG-75 cell line, which has been previously shown by our laboratory to express SERT 2,13 and to the SHSY-5Y neuroblastoma cell line, which does not express SERT 23 . As previously described, the compound of most interest from this study was the N-formyl-1,3-bis(4-methylthiophenyl)-2-propanamine (7a) (Fig.…”
Section: Sert-dependent Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of novel pyridines, dihydropyridone and N,N-di(1-aryl-2-propyl) amines described as route-specific byproducts associated with clandestine synthesis of 4-MTA and related amphetamines 12 were previously evaluated for SERT-selective cytotoxicity using human embryonic kidney cells overexpressing SERT, and two malignant cell lines; the DG-75 cell line, which has been previously shown by our laboratory to express SERT 2,13 and to the SHSY-5Y neuroblastoma cell line, which does not express SERT 23 . As previously described, the compound of most interest from this study was the N-formyl-1,3-bis(4-methylthiophenyl)-2-propanamine (7a) (Fig.…”
Section: Sert-dependent Cytotoxicitymentioning
confidence: 99%
“…Recently, a number of SERT-targeting ligands have been shown to induce apoptosis in a number of malignant cell lines including Burkitt's lymphoma [2][3][4][5][6] . SERT has also been implicated in serotonin-mediated apoptosis in Burkitt's lymphoma 7 and in the mechanism of cytotoxicity associated with the amphetamine analogues, fenfluramine 8 and 3,4-methylenedioxymethamphetamine (MDMA) 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…1) as a potential antiproliferative agent against BL cell lines, in particular, the resistant lymphoma cell line DG-75 had an EC 50 value in the low micromolar range following a treatment time of 72 hours with maprotiline [16,21]. It was found that maprotiline (and the SSRI fluoxetine) induce Type II autophagic cell death in the resistant DG-75 cell line [21].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…BL cells have also been shown to overexpress the monoamine transporters SERT and NET to various degrees. However their involvement in the antiproliferative effect of monoamine transporter ligands has been disputed and is unlikely to play an important role [16].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The recent discovery that some antidepressants show a wide range of pharmaceutical activities such as antidepressants [2], antiproliferative agent against BL cell lines [3] and anti-multi-drug resistance (MDR) activity on cancer cells and the malaria strain P. Falciparum [4][5][6] led many groups work on the synthesis of novel 9,10-dihydro-9,10-ethanoanthracene derivatives [2,[7][8][9][10][11][12][13]. The asymmetric unit of the title structure contains one independent molecule.…”
Section: Discussionmentioning
confidence: 99%